Pengembangan media pembelajaran berbasis android “Smart Volly” untuk pembelajaran bola voli siswa kelas VII SMP Negeri 1 Ulujami - Netto Rizki Aprilianto; Utvi Hinda Zhannisa; Asep Ardiyanto (YLPK Mahardhika, 2021)
Students feel less interested in learning volleyball. This is because the learning system during the pandemic is boring because it is only through books and worksheets. Therefore, this research is aimed at developing an android-based learning media, namely SMART VOLLY to assist teachers in implementing volleyball learning material. This research includes the type of research development or Research and Development. It is carried out in stages: looking for potential problems, collecting data, designing products, validating designs, improvingdesigns, testing products, and testing usage. The validation process was carried out on media experts, material experts, 2 teacher responses, testing on 15 small-scale students, and 32 large-scale students. The research subjects were students of class VII A of SMP Negeri 1 Ulujami. Data collection techniques were carried out using a questionnaire. Technical analysis of data with descriptive qualitative and quantitative descriptive percentages. The results of the study were obtained based on the validation results of a) media experts, the display aspect was 78% or very feasible, the programming aspect was 82% or very feasible; b) material expert, the quality aspect of the learning material is 93% or very feasible, the content aspect is 94% or very feasible; c) teacher response 94% or very decent; and d) student response 86.9% or very decent. Thus, it can be concluded that the SMART VOLLY android application is declared very suitable for use as a medium for learning volleyball material for seventh-grade junior high school students.